Notary in Indonesia: How Are State Fundamental Values Reflected in Law and Professional Ethics? - Mahadewi, I Gusti Agung Ika Laksmi; Padmawati, Ni Komang Tari; Rwa Jayantiari, I Gusti Agung Mas (Udayana Journal of Law and Culture, 2022)
In recent times, the public has concerns addressed to the position of notary due to cases of violations of law and code of ethics by notaries. This situation leads to a question on the internalization of state values and ethical principles by a notary.  This paper aims at elaborating on the position of a Notary in the Indonesian legal system, and further, analyzing the reflection of Pancasila values in Law on Notary and the Code of ethics of Notary. It is legal research that primarily analyzes the normative contents of applicable Indonesian law and regulations that regulate the issue of a notary, Articles of Association of the Indonesian Notary Association, Code of Ethics of Notary, as well as relevant court decisions.  This article concludes that the Indonesian legal system granted notary a status as a public official authorized to make authentic deeds and other authorities as intended in Indonesian Notary Law. In addition, the legal system also requires notary, as a legal profession, to become a member of Ikatan Notaris Indonesia (INI), the only legitimate notary association in Indonesia. Normatively, both Indonesian Notary Law and the Code of Ethics of Notary have adopted the values contained in the precepts of Pancasila which in general require a notary to have good moral integrity, character, and personality; uphold professional ethics; prioritize services for the interests of the community and the state; have social concerns; and carry out tasks without merely focused on economic benefits.